Conservation of Plastics (materials science, degradation and preservation) - San Andrés Moya, Margarita (Ge-conservacion, 2011)
Reseña del libro: Conservation of Plastics (materials science, degradation and preservation) Yvonne Shashoua Butterworth – Heinemann Oxford, 2008 285 páginas más 14 páginas introductorias, ilustraciones, tablas, esquemas, 195 x 250 cm ISBN: 978-0-7506-6495-0